Incidentally Diagnosed Extraluminal Leiomyosarcoma of Infrarenal Inferior Vena Cava: A Case Report and Literature Review from a Radiologist’s Perspective - A, Ebinesh; Ashta, Aanchal; Satyam, Satyam; Shanker Pradhan, Gaurav; Sharma, Rohin; Das, Prince (Acta medica Lituanica, 2022)
Background: Vascular leiomyosarcoma is a rare but most common vascular tumor of the inferior vena cava. Case presentation: We present the case of an incidentally diagnosed extraluminal leiomyosarcoma of the inferior vena cava in a 62 year old patient who presented with abdominal pain following blunt trauma. Ultrasonography showed a lobulated hypoechoic lesion in the upper abdomen. Computed tomography (CT) and magnetic resonance imaging (MRI) showed a circumscribed lobulated near homogeneously enhancing retroperitoneal lesion in anterior relation to the infrarenal inferior vena cava, right paramedian in location with imperceptible vena caval lumen at the site of maximum contact. In positron emission tomography (PET) CT the lesion showed mild fluorodeoxyglucose (FDG) uptake with no distant metastases. CT guided biopsy with immunohistochemical analysis showed leiomyosarcoma. Patient underwent surgical resection with inferior vena cava reconstruction. Conclusions: Leiomyosarcoma of the inferior vena cava is a rare tumor of vascular origin. Imaging plays an imperative role in the diagnosis and preoperative evaluation. This article also provides a comprehensive literature review of the radiological features of inferior vena caval leiomyosarcoma that would aid in optimal preoperative characterization and evaluation.